The Influence Of The Board Of Commissioners And Managerial Ownership On Intellectual Capital Disclosure In Banking Companies On The Indonesia Stock Exchange - rosidawaty, Rosidawaty rosi; Soenaryo, Dede; Wangsih, Ingkak Chintya; Permananingrum, Ervina Yennie; Haromain, Achmad (Balance Vocation Accounting Journal, 2024)
This research aims to determine the influence of the board of commissioners and managerial ownership on intellectual capital disclosure. The data analysis method used is multiple panel regression analysis so that the direction and magnitude of the influence of the independent variable on the dependent variable can be clearly depicted. This research used Eviews Student 12. The research sample consisted of 23 banking companies from 47 companies listed on the Indonesian stock exchange for the 2018- 2022 period. Sampling with certain criteria. The research results show that: 1). The board of commissioners has a negative and insignificant effect on intellectual capital disclosure; 2). Managerial ownership has a positive and significant effect on intellectual capital disclosure; 3). The board of commissioners and managerial ownership have a positive and significant effect on intellectual capital discussion simultaneously.